Conservation Laws of a Gardner Equation with Time-dependent Coefficients - Bruzón, M.S.; Gandarias, M.L.; Rosa, R. de la (Journal of Applied Nonlinear Dynamics, 2026)
A study of a variable-coefficient Gardner equation is carried out. The subclasses of the equation which are nonlinear self-adjoint have been determined. Conservation laws have also been obtained using two different methods: the direct method of the multipliers and Ibragimov’s theorem based on nonlinear self-adjointness of the equation. It has shown that for this equation conservation laws obtained by using both methods are equivalent.